Overview of Bilateral Retinoblastoma at Dr. M. Djamil General Hospital, Padang, Indonesia - Ficky Ferliando; Ardizal Rahman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Retinoblastoma is the most common intraocular primary malignant tumor in children. In the United States, cases of retinoblastoma are estimated to be found in 1 in 18,000 children under 5 years. The incidence of retinoblastoma ranges from 1:14.00 to 1:34.000 live births. The highest incidence occurs in developing countries. This study aimed to provide a clinical picture of bilateral retinoblastoma at Dr. M. Djamil General Hospital, Padang, Indonesia, as basic data for further policy-making in order to optimize services related to the management of bilateral retinoblastoma. Methods: This study was a descriptive observational study with 29 study subjects. Sociodemographic, clinical, and management data are presented descriptively. Data analysis was performed with the help of SPSS software version 25. Results: Based on the age group, the majority of bilateral retinoblastoma cases were less than 5 years old, with the most age range being 3-4 years. The majority of therapeutic management for cases of bilateral retinoblastoma is exenteration in combination with chemotherapy. Conclusion: A combination of surgery and chemotherapy is the most frequently used treatment for bilateral retinoblastoma at Dr. M. Djamil General Hospital, Padang, Indonesia.